PERAN KEPALA DAERAH BERDASARKAN UU NO.32 TAHUN 2004 TERHADAP KEMAJUAN DI KOTA SEMARANG - Ansyahri Darma Tri Jati; Dyah Listyorini (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2022)
This research is entitled The Role of Regional Heads Based on Law No. 32 of 2004 on Progress in Semarang City with the problems (1) What is the role of regional heads on regional progress in Semarang City? (2) What are the impacts of progress and obstacles for regional heads in the city of Semarang? This study uses a qualitative approach that is descriptive analysis with normative juridical methods, namely by using research materials from secondary data collected through library studies, in addition to field research by the author through interviews with West Semarang District employees. The conclusion of this research is (1) The role of the Regional Head is very important to implement Law No. 32 of 2004, especially in the sector of regional autonomy and development for the progress of the city of Semarang itself (2) Let's always maintain and monitor so that the region is always full of activities to improve the efficiency of local government services that are oriented to the community itself and to realize people's welfare and increase human resources through creative and innovative activities. (3) Encouraging the emergence of independence driven by creativity and innovation by optimizing various potential sources, both human resources and natural resources, which will greatly support and enhance national development within the framework of the Unitary State of the Republic of Indonesia. (4) Improving the efficiency of government administration through a harmonious relationship between the regional government and the central government as well as the DPRD as well as the community to create a synchronous management system relationship.